The Impact of Perceived Advertising Spending and Price Promotion on Brand Equity:A Case of ABC Brand - Kevin Edward Nurcahya (iBuss Management, 2014)
Intense competition in Indonesian beverage industry lead many corporations to spend trillion rupiah on marketing communication, such as advertising and price promotion with the hope of increasing brand equity. However, the question is whether promotional activities in this industry amplify or attenuate the brand equity of a product. Therefore, this paper aims to model the impact of perceived advertising spending and price promotion on brand equity, measured through consumer perceptions, specifically in the case of ABC brand brand. This study includes explanatory research with the samples taken for one of PT XYZ’s flagship products, ABC brand. All of the respondents are Surabaya people, altogether 123 respondents. The sampling method used was simple random sampling. A quantitative approach was employed, using 25-item, 5-point Likert scale questionnaires. Multiple regression analysis methods in SPSS 21 program were used to examine the result. The result has several conclusions. First, perceived advertising spending has significant effect on brand equity and three out of for brand equity dimensions, namely perceived quality, brand awareness and brand loyalty. Second, price promotion also has significant impact on brand equity and three out of four dimensions of brand equity: brand loyalty, perceived quality and brand association. Keywords: Perceived advertising spending, price promotion, brand equity, Surabaya